Knowledge about stroke among adults in Sharjah, United Arab Emirates - Karkout, Rami A.; Shamaa, Omar; Al Ammour, Sara T.; Abd Elmaged, Rana S.; Al Kassar, Lujain A.; Al Ali, Meera N. (International Journal of Research in Medical Sciences, 2019)
Background: In UAE, stroke is the second leading cause of disability after RTA, where annually 8,000 to 10,000 patients get a stroke. Our aim is to identify the knowledge levels of stroke among Sharjah’s adult citizens. Methods: Using self-administered questionnaires, in a cross-sectional design, a non-probability convenience sampling method was used to enrol subjects. Eligible subjects were above 18 years of age, comprehended Arabic or English, and are currently residing in Sharjah. The questionnaire was 17 questions structured in 5 sections which included: demographics, general knowledge, knowledge of signs and symptoms, risk factors, and appropriate response towards stroke. SPSS V.22 was used to analyse the data. Percentages, means, and ANOVA were used. A P-value less than 0.05 was considered to be statistically significant. Results: The study included 426 subjects, mean age was 35.1 years, 65.2% were females. 51.8% of the subjects claimed they know what stroke is, out of whom 24.3% provided incorrect descriptions. The mean knowledge level of signs and symptoms was 55.4%, and of risk factors was 40.6%. Visual disturbance was the least identified of the five signs and symptoms (38.0%). Female gender, African American race, and age above 60, were the least identified of the 8 risk factors (4.7%, 3.5%, 19.8% respectively). Better knowledge was associated with increased age and higher education. Conclusion: The majority of the sample showed an average to low level of knowledge. Such results indicate the importance of implementing more awareness programs that target younger age groups in the community.